Singapore : Report on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses findings of the Report on Observance of Standards and Codes on Singapore. The Monetary Authority of Singapore (MAS) shows a very high level of compliance with the Basel Core Principles and demonstrates a strong commitment by MAS to their implementation. As a large financial center, MAS is well aware of the risks posed by a financial system that is significantly larger than the economy of Singapore, and comprised primarily of branches of foreign institutions operating in non-Singapore dollars. MAS has also set a high standard for approving foreign entrants, applying the same prudential framework to foreign branches as to its own locally incorporated banks.